Temperature-Dependent Direct Enantioconvergent Silylation of a Racemic Cyclic Allylic Phosphate by Copper(I)-Catalyzed Allylic Substitution - Delvos, Lukas B.; Oestreich, Martin (Synthesis, 2015)
The near-quantitative transformation of a racemic cyclic allylic phosphate to a highly enantiomerically enriched allylic silane by allylic substitution with a silicon nucleophile is reported. The reaction is catalyzed by a chiral NHC–copper(I) complex. Experimental analysis revealed a rare case of a direct enantioconvergent transformation where the enantiomeric allylic phosphates converge to the same allylic silane by two distinctive SN2′ pathways with opposite diastereofacial selectivity.
Keywords: allylic substitution; copper; enantioselectivity; N-heterocyclic carbenes; silicon